The cinema of James Cameron : bodies in heroic motion - Clarke, James, 1972- (Directors' cuts., 2014)
This timely volume explores the massively popular cinema of writer-director James Cameron. It couches Cameron's films within the evolving generic traditions of science fiction, melodrama, and the cinema of spectacle. The book also considers Cameron's engagement with the aesthetic of visual effects and the 'now' technology of performance-capture which is arguably moving a certain kind of event-movie cinema from photography to something more akin to painting. This book is explicit in presenting Cameron as an authentic auteur, and each chapter is dedicated to a single film in his body of work, from The Terminator to Avatar. Space is also given to discussion of Strange Days as well as his short films and documentary works. -- Provided by publisher.